2008
DOI: 10.1007/s00125-008-1050-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation between the mouse and human glucose-6-phosphatase catalytic subunit gene promoters results in differential activation by peroxisome proliferator activated receptor gamma coactivator-1α

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Interestingly, in the same year, HNF-4α was reported to mediate this activation by binding to the region between −76 and −64 of the mouse G6Pase promoter (Boustead et al 2003). In addition to the HNF-4α-binding site located between −76 and −64, a 3 bp sequence discovered by the same team was found to be a crucial site for HNF-4α-binding activity (Schilling et al 2008). In addition, many other transcription factors and coactivator proteins, such as DAX-1 (dosage-sensitive sex reversal, adrenal hypoplasia critical region, on chromosome X, gene 1), sterol regula tory element-binding proteins (SREBPs), vanin-1, cAMP, xenobiotic-metabolizing cytochrome P450 (CYP) 2A5 enzyme, HNF-6, and FOXO1, also contribute to the PGC-1α/HNF-4α-mediated transcriptional regulation of the gluconeogenic genes (Yamamoto et al 2004, Beaudry et al 2006, Arpiainen et al 2008, Schilling et al 2008, Nedumaran et al 2009, Dankel et al 2010.…”
Section: Hepatocyte Nuclear Factor-4αmentioning
confidence: 96%
“…Interestingly, in the same year, HNF-4α was reported to mediate this activation by binding to the region between −76 and −64 of the mouse G6Pase promoter (Boustead et al 2003). In addition to the HNF-4α-binding site located between −76 and −64, a 3 bp sequence discovered by the same team was found to be a crucial site for HNF-4α-binding activity (Schilling et al 2008). In addition, many other transcription factors and coactivator proteins, such as DAX-1 (dosage-sensitive sex reversal, adrenal hypoplasia critical region, on chromosome X, gene 1), sterol regula tory element-binding proteins (SREBPs), vanin-1, cAMP, xenobiotic-metabolizing cytochrome P450 (CYP) 2A5 enzyme, HNF-6, and FOXO1, also contribute to the PGC-1α/HNF-4α-mediated transcriptional regulation of the gluconeogenic genes (Yamamoto et al 2004, Beaudry et al 2006, Arpiainen et al 2008, Schilling et al 2008, Nedumaran et al 2009, Dankel et al 2010.…”
Section: Hepatocyte Nuclear Factor-4αmentioning
confidence: 96%
“…Recent study has shown that insulin signaling stimulates S6/K1 kinase, which phosphorylates PGC-1a at Ser568 and Ser572 in hepatocytes, resulting in the loss of ability to interact with HNF4a (Lustig et al, 2011). PGC-1a seems to activate G6PC1 through the interaction with HNF4a-bound HNF4-binding site in mouse gene fairly well; however, this is not the case for human G6PC1 due to variation of nucleotide sequence adjacent to the HNF4a-binding site which markedly reduces PGC-1a-mediated transcriptional activation (Schilling et al, 2008).…”
Section: Peroxisome Proliferator-activated Receptor Coactivator-1amentioning
confidence: 90%
“…Schilling and colleagues demonstrated that this species-specific difference could be explained by a 3 bp sequence variation, located immediately adjacent to a consensus nuclear hormone receptor half-site that is perfectly conserved between the mouse and human G6PC promoters. 43 With gel retardation experiments, Schilling and her colleagues demonstrated that this 3 bp variation in the human G6PC promoter extinguishes HNF-4α binding to the half-site. DHEA is a potent peroxisome proliferator and a known inducer of PGC-1α.…”
Section: Of Mice and Menmentioning
confidence: 99%